Physician Aid in Dying for Dementia: The Problem With the Early vs. Late Disease Stage Distinction - Nicolini, Marie Elisabeth (Frontiers in Psychiatry, 2021)
Background: Physician aid in dying based on dementia is a contentious, highly debated topic. Several countries are considering extending their existing laws to include requests in incompetent patients based on a previously written advance directive. Discussions about this issue often invoke a distinction based on disease stage. The Dutch practice uses this distinction in classifications of dementia PAD cases and in guidance for clinicians. This paper explores the problem with this distinction for assessments of persons at the margins of competence. The problem: Dutch guidance for clinicians uses an early versus late-stage disease distinction to refer to requests from competent and incompetent persons. However, the use of disease stages is problematic, both conceptually and empirically. Conceptually, because it goes against very functional model of competence that guidance recognizes. Empirically, because it creates problems for classifying and evaluating patients at the margins of competence. Possible ways forward: Classification of cases and guidance should be based on competence, not disease stage. This requires rethinking decision-making for patients with dementia. Several possibilities are described, ranging from redefining the scope and role of advance directives in this context to exploring different types of decision-making frameworks.